2015
DOI: 10.1038/srep12999
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer of zeste homolog 2 silencing inhibits tumor growth and lung metastasis in osteosarcoma

Abstract: The enhancer of zeste homolog 2 (EZH2) methyltransferase is the catalytic subunit of polycomb repressive complex 2 (PRC2), which acts as a transcription repressor via the trimethylation of lysine 27 of histone 3 (H3K27me3). EZH2 has been recognised as an oncogene in several types of tumors; however, its role in osteosarcoma has not been fully elucidated. Herein, we show that EZH2 silencing inhibits tumor growth and lung metastasis in osteosarcoma by facilitating re-expression of the imprinting gene tumor-suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 57 publications
5
38
0
2
Order By: Relevance
“…A limited number of studies have indicated that it may be plausible that targeting abnormal HMTs and HDMTs in cancer cells may partly contribute to the treatment of osteosarcoma. For example, EZH2 methyltransferase, which trimethylates H3K27 serves oncogenic roles in human osteosarcoma (6), and treatment with EZH2 inhibitor leads to a marked reduction of cell viability in osteosarcoma (34); increased expression of the HMT NSD3 has been observed in osteosarcoma, and NSD3 is likely to serve key roles in the development of osteosarcoma (8). Another study reported that LSD1 is overexpressed in osteosarcoma, and treatment of osteosarcoma cells with the LSD1 inhibitor tranylcypromine reduced cell growth (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited number of studies have indicated that it may be plausible that targeting abnormal HMTs and HDMTs in cancer cells may partly contribute to the treatment of osteosarcoma. For example, EZH2 methyltransferase, which trimethylates H3K27 serves oncogenic roles in human osteosarcoma (6), and treatment with EZH2 inhibitor leads to a marked reduction of cell viability in osteosarcoma (34); increased expression of the HMT NSD3 has been observed in osteosarcoma, and NSD3 is likely to serve key roles in the development of osteosarcoma (8). Another study reported that LSD1 is overexpressed in osteosarcoma, and treatment of osteosarcoma cells with the LSD1 inhibitor tranylcypromine reduced cell growth (35).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that histone methylation, a mechanism for modifying chromatin structure, contributes to aberrant transcriptional regulation and oncogenic signaling pathways in osteosarcoma (4). Furthermore, increased expression of histone methyltransferases (HMTs), including G9a, enhancer of zeste homolog 2 (EZH2), nuclear SET domain-containing 3 (NSD3), protein arginine N-methyltransferase 1, and coactivator-associated arginine methyltransferase 1, contribute to osteosarcoma development (5)(6)(7)(8)(9)(10). These data suggested that genes encoding histone methylation modifiers, HMTs and histone demethylases (HDMTs), may serve key roles in the development and progression of OS.…”
Section: Introductionmentioning
confidence: 99%
“…Samples containing >50% of RanBP9 or TSSC3-positive cells were designated as 'positive expression'. 48, 49, 50 Lung metastases and local recurrence were diagnosed by both imaging and pathology, and the surgical margins were classified according to the Enneking staging system. Patients with primary osteosarcoma were classified as with or without metastasis at diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Enhancer of zeste homolog 2 (EZH2) is the catalytic subunit of polycomb repressive complex 2. The knockdown of EZH2 caused a decrease in anti-apoptotic Bcl-2 and an increase in pro-apoptotic Bax and Bak proteins, as well as an increase in the expression of cytochrome C in the cytosol; indicating that EZH2 suppressed cell apoptosis through the intrinsic apoptotic pathway [77]. Additionally, EZH2 could inhibit cell apoptosis by coordinating the epigenetic silencing of two proapoptotic microRNAs (miRNA), miR-205 and miR-31 [78].…”
Section: Programmed Cell Death In the Treatment Of Osteosarcomamentioning
confidence: 99%